A node discovery protocol for ad hoc underwater acoustic networks. Issue 3 (14th February 2012) - Patil, Ashish; Stojanovic, Milica; Gerla, Mario; Maggiorini, Dario; Palazzi, Claudio E.
ABSTRACT Motivated by the advances in acoustic modem technology and the growing number of applications that call for ad hoc deployable autonomous underwater systems (floating sensors, crawlers, vehicles), we address the problem of network initialization upon deployment. A neighbor discovery protocol is proposed, whose goal is to establish communication links over a large area, with a finite power budget that mandates multi‐hopping to provide full coverage. The protocol uses random access to eliminate the need for scheduling (i.e., enable system operation without a global clock reference) and power control to ensure that full connectivity is provided using shortest links (i.e., to conserve batteries and prolong the system's lifetime). Transmit power allocation takes into account the acoustic propagation loss, while additional large‐scale variation in the average received power is modeled via log‐normal fading which is confirmed by experimental observations. System performance is assessed through simulation, by measuring the energy consumption, time to completion, and reliability in the presence of fading. Fading is shown to have a degrading effect on the system reliability, and protocol adjustments are proposed to recover the performance under the constraint on maximum power. The key features of the protocol are simplicity of implementation and efficient use of power.Copyright © 2012 John Wiley & Sons, Ltd.